2014
DOI: 10.1007/s13730-014-0121-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic renal failure due to amyloid nephropathy caused by chronic infection after total hip replacement

Abstract: A 75-year-old woman was admitted to our hospital because of proteinuria, pitting edema on the foot, and renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(22 reference statements)
0
9
0
1
Order By: Relevance
“…The most severe complication of joint arthroplasty is periprosthetic infection, which can lead to complications such as sepsis, renal amyloidosis, dystrophic changes in parenchymatous organs, and the appearance of septicopyemic foci [9,17,18]. Two-stage revision remains the gold standard for the treatment of deep periprosthetic hip infection [19].…”
Section: Discussionmentioning
confidence: 99%
“…The most severe complication of joint arthroplasty is periprosthetic infection, which can lead to complications such as sepsis, renal amyloidosis, dystrophic changes in parenchymatous organs, and the appearance of septicopyemic foci [9,17,18]. Two-stage revision remains the gold standard for the treatment of deep periprosthetic hip infection [19].…”
Section: Discussionmentioning
confidence: 99%
“…Okuda, et al 9 reported that the most frequent underlying inflammatory disease provoking AA amyloidosis was rheumatoid arthritis (60.3%). Chronic infection, including postoperative refractory infection, caused AA amyloidosis in 4.5% of cases 10 . Li, et al 11 described a case of chronic diverticulitis inducing AA amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infection, including postoperative refractory infection, caused AA amyloidosis in 4.5% of cases. 10 Li, et al 11 described a case of chronic diverticulitis inducing AA amyloidosis. In the past, tuberculosis and leprosy were the major source of AA amyloidosis.…”
Section: F I G U R E 3 Gastric Perforation Withmentioning
confidence: 99%
“…5 Artificial THA is also employed for the treatment of various diseases such as rheumatoid arthritis, congenital hip dysplasia, femoral head aseptic necrosis/ischemic necrosis, femoral neck fracture, and hip tumors. 6–11…”
Section: Introductionmentioning
confidence: 99%
“…5 Artificial THA is also employed for the treatment of various diseases such as rheumatoid arthritis, congenital hip dysplasia, femoral head aseptic necrosis/ischemic necrosis, femoral neck fracture, and hip tumors. [6][7][8][9][10][11] Although relatively rare, prosthetic hip dislocation is one of the most common postoperative complications in patients undergoing THA. The incidence of this serious complication is second only to that of aseptic loosening of artificial joints.…”
Section: Introductionmentioning
confidence: 99%